Audiologic and Otologic Clinical Manifestations of Loeys-Dietz Syndrome: A Heritable Connective Tissue Disorder. (February 2022) - Jeon, Jun W.; Christensen, Julie; Chisholm, Jennifer; Zalewski, Christopher; Rasooly, Marjohn; Dempsey, Caeden; Magnani, Alaina; Frischmeyer-Guerrerio, Pamela; Brewer, Carmen C.; Kim, Hung Jeffrey
Objective: Loeys-Dietz syndrome (LDS) is a rare genetic connective tissue disorder resulting from TGF-ß signaling pathway defects and characterized by a wide spectrum of aortic aneurysm, arterial tortuosity, and various extravascular abnormalities. This study describes the audiologic, otologic, and craniofacial manifestations of LDS. Study Design: Consecutive cross-sectional study. Setting: Tertiary medical research institute. Methods: Audiologic and clinical evaluations were conducted among 36 patients (mean ± SD age, 24 ± 17 years; 54% female) with genetically confirmed LDS. Cases were categorized into genetically based LDS types 1 to 4 ( TGFBR1, TGFBR2, SMAD3, TGFB2, respectively). Audiometric characteristics included degree and type of hearing loss: subclinical, conductive, mixed, and sensorineural. Results: LDS types 1 to 4 included 11, 13, 5, and 7 patients, respectively. In LDS-1, 27% had bilateral conductive hearing loss; 9%, unilateral mixed; and 36%, subclinical. In LDS-2, 38% had conductive hearing loss and 38% subclinical. In LDS-3 and LDS-4, 40% and 43% had bilateral sensorineural hearing loss, respectively. Degree of hearing loss ranged from mild to moderate. Bifid uvula was observed only in LDS-1 (55%) and LDS-2 (62%). Submucosal/hard cleft palates were primarily in LDS-1 and LDS-2. Posttympanostomy tympanic membrane perforations occurred in 45% (10/22 ears) of LDS-1 and LDS-2. There were 4 cases of cholesteatoma: 3 middle ear (LDS-1 and LDS-2) and 1 external ear canal (LDS-3). Conclusion: Conductive hearing loss, bifid uvula/cleft palate, and posttympanostomy tympanic membrane perforation are more common in LDS-1 and LDS-2 than LDS-3 and LDS-4, while sensorineural hearing loss was present only in LDS-3 and LDS-4. These LDS-associated key clinical presentations may facilitate an early diagnosis of LDS and thus prompt intervention to prevent related detrimental outcomes.